Cardiopulmonary Exercise Testing: Deciphering Cardiovascular Complications in Systemic Sclerosis - Ailia Giubertoni; Mattia Bellan; Luca Cumitini; Giuseppe Patti (Reviews in Cardiovascular Medicine)
Cardiac manifestations in systemic sclerosis (SSc) are variable and are associated with a poor prognosis, frequently resulting in impaired right ventricular function and heart failure. A high proportion of patients with SSc experience pulmonary arterial hypertension (PAH), interstitial lung disease, or myocardial involvement, all of which can lead to exercise intolerance. In this context, cardiopulmonary exercise testing (CPET) is a useful tool for diagnosing exercise intolerance, elucidating its pathophysiology, and assessing its prognosis. CPET can also identify patients with SSc at higher risk of developing PAH. Despite its utility, current guidelines for CPET do not include the evaluation of patients with SSc, nor do standard SSc management guidelines consider CPET in the clinical work-up. This review summarizes the development, supporting evidence, and application of CPET in assessing cardiac involvement in patients with SSc.